Digital library evaluation using the Human-Organization-Technology Fit Model - Siswantoro, Siswantoro (Daluang: Journal of Library and Information Science, 2023)
Purpose. This research aims to evaluate the Rumah Ilmu website which is used as digital library media at Universitas Negeri Semarang using the Human-Organization-Technology-Fit (HOT-Fit) Model.Methodology. The method used is clause associative which functions to test the relationship between variables. The sampling technique used simple random sampling and the sample size was 62 respondents. The data collection technique uses a questionnaire distributed via Google Forms. The data analysis technique with correlation analysis.Results and discussion. The results of the validity and reliability tests show that all question items are declared valid. The results of the correlation test show that overall the relationship between the three elements in the HOT-Fit Model is in the strong and very strong categories.Conclusions. The research results concluded that the significance value of the HOT and net benefit shows a value of 0.00 < 5% with a correlation coefficient of 0.878. This indicated that the Rumah Ilmu website in supporting digital libraries was quite good. However, improving the quality of the system must continue to be carried out in the future so that it can provide wider benefits to users.